Beina- og liðasýkingar barna á Íslandi af völdum baktería á tímabilinu 1996-2005 - Ásgeir Þór Másson; Þórólfur Guðnason; Guðmundur K. Jónmundsson; Helga Erlendsdóttir; Karl G. Kristinsson; Már Kristjánsson; Ásgeir Haraldsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2011)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) Objective: The main objective was to determine the incidence and causative pathogens of osteomyelitis and septic arthritis in Icelandic children, as well as presenting symptoms and diagnosis. Methods: A nationwide retrospective review was done of all children <18 year old, 1996-2005. Subjects were divided into three equal age groups, 0-5, 6-11 and 12-17 years old. Cultures were reviewed and postive and negative cases compared. Results: Over the study period 220 cases were identified, 161 osteomyelitis and 59 septic arthritis cases. The incidence increased significantly over the period (p=0.019), mostly in the youngest age group (p<0.001) with osteomyelitis. Incidence of cases with a pathogen identified was unchanged over the period while culture negative cases increased significantly (p<0.001). Median age for osteomyelitis (6,1 years) was higher than in cases of septic arthitis (1,8 years) (p=0.003). A pathogen was identified in 59% of cases with osteomyelitis and 44% with septic arthritis. S. aureus was most common (65% and 27%, respectively) and K. kingae was second most common pathogen (7% and 11%, respectively). Methicillin resistant S. aureus was not identified. The tibia and knee were the predominant sites for osteomyelitis and septic arthritis respectively. Conclusions: An increased incidence was found in the youngest age group with osteomyelitis, especially in cases without a pathogen identified. The most commonly cultured pathogen was S. aureus, followed by K. kingae. A more sensitive technique to identify pathogens might be indicated in culture negative cases. Tilgangur: Markmið rannsóknarinnar var að kanna nýgengi, sýkingarvalda, einkenni og greiningaraðferðir beina- og liðasýkinga í börnum á Íslandi. Efniviður og aðferðir: Rannsóknin var afturskyggn og náði til barna yngri en 18 ára sem lögðust inn vegna sýkinganna á tímabilinu 1996-2005. Upplýsingum var safnað úr sjúkraskrám. ...